Association Between C-Reactive Protein and Risk of Amyotrophic Lateral Sclerosis: A Mendelian Randomization Study - Zhu, Yahui; Li, Mao; Zhang, Jinghong; Huang, Xusheng (Frontiers in Genetics, 2022)
Background: Until now, the relationship between C-reactive protein(CRP) levels and amyotrophic lateral sclerosis (ALS) risk has not been fully established. It is necessary to assess whether there is a causal relationship between C-reactive protein levels and ALS risk. Objective and Methods: We aimed to determine whether CRP has causal effects on risk of ALS. In this present study, summary-level data for ALS (20,806 cases and 59,804 controls) was obtained from large analyses of genome-wide association studies. For instrumental variables, 37 single nucleotide polymorphisms that had been previously identified to be related to CRP levels were used, including 4 SNPs of conservative CRP genetic variants and 33 SNPs of liberal CRP genetic variants. MR estimates were calculated using the inverse-variance weighted method, supplemented by MR-Egger, weighted median, and MR-PRESSO methods. Results: There was no significant causal relationship between genetically predicted CRP levels and ALS risk ( OR= 1.123, 95% CI = 0.963–1.309, P = 0.139) and results for the conservative CRP instruments were consistent (OR=0.964, 95% CI = 0.830–1.119, P = 0.628). Pleiotropic bias was not observed in this study. Conclusions: This study suggests that genetically predicted CRP levels may not be a causal risk factor for ALS.